2006
DOI: 10.1016/j.cropro.2005.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of white grubs (Coleoptera: Scarabaeidae) on groundnut in southern India

Abstract: 1Scarab species associated with groundnuts were surveyed in Andhra Pradesh, Karnataka and 2 Tamil Nadu, southern India, between 1995 and 2001. Scarab adults were collected from trees 3 on which they were feeding and/or mating, and larvae (white grubs) from groundnut fields. 4Holotrichia species, especially H. reynaudi and H. serrata were the major species associated 5 with groundnut. H. reynaudi predominated in the central Deccan area, while H. serrata was 6 most abundant in areas to the south and west. A new,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…While host plants like Z. jujuba, Z. mauritiana and Z. xylopyra were confirmed as hosts for feeding for H. rustica and H. mucida, other plants like A. leucophloea and A. catechu seem to be hosts for mating (N. Kulkarni, 2002Kulkarni, -2005, unpublished observation), as Anitha et al (2006) have reported in cases of various scarab species in southern India. Kulkarni et al (2007) have recently reported similar observations for co-existing scarabaeid, S. ruficollis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…While host plants like Z. jujuba, Z. mauritiana and Z. xylopyra were confirmed as hosts for feeding for H. rustica and H. mucida, other plants like A. leucophloea and A. catechu seem to be hosts for mating (N. Kulkarni, 2002Kulkarni, -2005, unpublished observation), as Anitha et al (2006) have reported in cases of various scarab species in southern India. Kulkarni et al (2007) have recently reported similar observations for co-existing scarabaeid, S. ruficollis.…”
Section: Discussionmentioning
confidence: 93%
“…Indian chafer beetles are known to become active with the onset of monsoon in a variety of cropping and forestry systems (Thakur, 1988(Thakur, , 1993Meshram et al, 1990;Yadava & Sharma, 1995;Anitha et al, 2006). Garg et al (2005) and Kulkarni et al (2007) have recently provided substantial data on species affecting forest nurseries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the adult (beetle) of S. ruficollis causes minor damage by defoliating leaves of horticultural and forest species, the subterranean larval stage (white grub) inflicts severe damage to root systems. S. ruficollis beetle defoliates leaves of tamarind and rose (Roonwal, 1954) and feeds on grapevine (Batra et al, 1973), Prosopis cineraria (Parihar &Singh, 1998) Acacia, ber, tamarind andneem (Musthak Ali, 2001;Anitha et al, 2006). Its grubs damage roots of prunus, sugarcane, millets, grapes and groundnut (Kumar, 1971;Musthak Ali, 2001;Kapadia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…discovered 100 years ago by Mednicho has a rather e entomopathogenic fungus, M. anisopliae, it causes serious damage to in sugarcane root system and damage is caused by the larvae (Anitha et al, 2006). Apart from sugarcane they are also serious pests of groundnut and potato.…”
Section: Introductionmentioning
confidence: 99%